Promising young woman [videorecording (DVD)] - Fennell, Emerald, 1985-; Fennell, Emerald, 1985-; Fennell, Emerald, 1985-; Mulligan, Carey, 1985-; Burnham, Bo, 1990-; Brie, Alison (Universal Pictures Home Entertainment, 2021)
A young woman who has been traumatized by past events seeks out revenge.